Review article: Role of magnesium sulphate in the management of Irukandji syndrome: A systematic review. (17th October 2016) - Rathbone, John; Franklin, Richard; Gibbs, Clinton; Williams, David
Abstract: Signs of Irukandji syndrome (IS) suggest an underlying catecholamine storm with research demonstrating that Carukia barnesi venom causes a significant rise in adrenaline/noradrenaline serum levels. A systematic review was undertaken to ascertain the current evidence in treating IS with magnesium salts. A literature search was conducted using Scopus, Medline and ScienceDirect. Further articles were discarded via title description and/or abstract details. The remaining were read in full, and those identified as not having sufficient information regarding magnesium and patient outcomes were removed. Nine articles were identified. One article was a randomised controlled trial, which concluded that there appears to be no beneficial difference between those patients who received the magnesium sulphate (MgSO4 ) and those who received the placebo and recommended against the use of MgSO4 in IS. Of the remaining eight, one reported the failure of MgSO4 and the remaining seven were case series reporting varying success in its use. This systematic review found insufficient evidence to support any clear recommendation regarding the use of magnesium, but nor was there clear evidence to recommend against its use in IS. Two case series describe significant reduction in key symptoms and hypertension but are a non‐randomised albeit prospective series with the limitations accompanying this. The reporting of recrudescence of symptoms with reduction of dose does suggest a dose–response relationship. The evidence for the use of MgSO4 is at best anecdotal, and further research is required to either confirm its benefit or confirm the randomised controlled trial.